2001
DOI: 10.1093/toxsci/60.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Extrahepatic Tumor Induction by Peroxisome Proliferators in Male CD Rats

Abstract: Wyeth-14,643 (WY) and ammonium perfluorooctanoate (C8) belong to a diverse class of compounds which have been shown to produce hepatic peroxisome proliferation in rodents. From previous work, WY, but not C8, has been shown to produce hepatocellular carcinoma in rats, while C8 has been shown to produce Leydig cell adenomas. In addition, based on a review of bioassay data a relationship appears to exist between peroxisome-proliferating compounds and Leydig cell adenoma and pancreatic acinar cell hyperplasia/aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
251
4
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(267 citation statements)
references
References 25 publications
7
251
4
5
Order By: Relevance
“…We examined whether PFOA and PFOS affected intestinal tumorigenesis in the sensitive Min/+ mouse model, since adenomas in liver, testicular Leydig cells and pancreatic acinar cells were reported in male Sprague-Dawley and CD (only highest dose) rats after 2 year exposure to 0, 30 or 300 mg PFOA/kg diet, equal to mean daily doses of approximately 0, 1.5 and 15 mg/kg (Biegel et al, 2001;Butenhoff et al, 2012b). Originally reported significant increase in mammary lesions was comparable with controls and non-significant upon pathological reevaluation (Butenhoff et al, 2012b).…”
Section: Determination Of Internal Doses Of Pfoa and Pfosmentioning
confidence: 99%
See 2 more Smart Citations
“…We examined whether PFOA and PFOS affected intestinal tumorigenesis in the sensitive Min/+ mouse model, since adenomas in liver, testicular Leydig cells and pancreatic acinar cells were reported in male Sprague-Dawley and CD (only highest dose) rats after 2 year exposure to 0, 30 or 300 mg PFOA/kg diet, equal to mean daily doses of approximately 0, 1.5 and 15 mg/kg (Biegel et al, 2001;Butenhoff et al, 2012b). Originally reported significant increase in mammary lesions was comparable with controls and non-significant upon pathological reevaluation (Butenhoff et al, 2012b).…”
Section: Determination Of Internal Doses Of Pfoa and Pfosmentioning
confidence: 99%
“…Negative outcome in many in vitro and in vivo tests at gene and/or chromosome level indicated that PFOA is not genotoxic (EFSA, 2008). Thus, cancers detected after exposure to PFOA in liver, Leydig cells in testis and pancreas appears to be induced by non-genotoxic mechanisms, probably involving 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 30 peroxisome proliferation and activation of the peroxisome proliferator-activated receptor alpha (PPARα) and disturbance of the endocrine system (Biegel et al, 2001;EFSA, 2008;Klaunig et al, 2012).…”
Section: Determination Of Internal Doses Of Pfoa and Pfosmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some PFCs have been shown to have potential endocrinedisruptive activities in vertebrates. For example, perfluorooctanoic acid (PFOA) lowered concentrations of testosterone and cholesterol in serum in rats (Biegel et al, 2001;Martin et al, 2007), and modified the mRNA expression of genes associated with cholesterol biosynthesis and steroid metabolism in fetal mouse liver (Rosen et al, 2007). Exposure to perfluorodecanoic acid (PFDA) decreased circulating concentrations of testosterone and dihydrotestosterone in male rats (Bookstaff et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…PFOA and PFOS caused reductions in body weight, decreases in weight gain rate, and interference in lipid metabolism in rats (Lau et al 2007;Luebker et al 2002). The liver is considered the primary target organ for both acute and chronic exposure of the above two fluorochemicals, and their hepatotoxicity in rodents has been extensively studied, which mainly includes increased liver weight, induction of hepatocellular hypertrophy and lipid vacuolation, increased incidence of hepatocellular adenoma, and hypocholesterolemia (Biegel et al 2001;Butenhoff et al 2002;Seacat et al 2003). Additionally, the potential neurotoxicity, genotoxicity, molecular toxicity, and reproductive and developmental toxicities of PFOA and PFOS were demonstrated in recent toxicological studies (Austin et al 2003;Guruge et al 2006;Kennedy et al 2004;Lau et al 2004;Ren et al 2008).…”
mentioning
confidence: 99%